Improving Resilience to Climate Change for Caribbean Agriculture and Fisheries Sectors : 360° Resilience Background Paper - Makara, Nadia (World Bank, Washington, DC, 2021)
Caribbean small island developing states (SIDS) depend heavily on their limited natural resources, with the largest sectors generally being agriculture, fisheries, and tourism. Agriculture has always been an integral part of the Caribbean economy as a result of slavery and colonialism. In the post-emancipation period, a local peasantry of former slaves emerged and established independent communities with economies based on small-scale agriculture and other informal activities, including fishing, small-scale retailing, and charcoal-burning. At the same time, export agriculture based on sugar production persisted. The result was a system with a large-scale, export-oriented sector based on traditional plantation crops such as sugarcane and bananas juxtaposing a small-scale farming sector focusing on crops that are staples in local diets. This duality characterizes the agriculture sector in most Caribbean SIDs. Today, agriculture accounts for 23% of employment in the Caribbean, with Haiti having the largest share in the Caribbean of 62%. The majority of the Caribbean’s poor rely on agriculture for the provision of their livelihood. For example, nine of Jamaica’s fourteen parishes are over 70% rural while 65% of the population depends on agriculture as a major source of their livelihood.